Pointing Out Persuasion in Philemon Fifty Readings of Pauls Rhetoric From the Fourth to the Eighteenth Century - Tolmie, D. Francois (Mohr Siebeck, 2021)
Überzeugung in Philemon aufzeigen. Fünfzig Lesarten der Rhetorik des Paulus vom vierten bis zum achtzehnten Jahrhundert.
PublicationDate: 20211102
Keywords: New Testament -- Wirkungsgeschichte -- Slavery -- History of Interpretation -- Halakhah -- römisches Theater -- Pauline Literature -- Persuasion -- hopes in resurrection -- History of interpretation -- Pauline literature -- Neues Testament -- Array